Production of Hydrocarbon (C7-C20) from Hydrocracking of Fatty Acid Methyl Esters on Pd/Al-MCM-41 Catalyst - Hendro Juwono; Triyono Triyono; Sutarno Sutarno; Endang Tri Wahyuni; Harmami Harmami; Ita Ulfin; Fredy Kurniawan (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The production of hydrocarbon (C7-C20) and alcohol (C11-C19)  from fatty acid methyl esters (FAMEs) compound are produced from the transesterification of the seed oil of the Nyamplung that has been conducted by the catalytic hydrocracking using Al-MCM-41 and Pd2+-impregnated-Al-MCM-41 catalysts. The performance of catalysts were compared by various analysis including the acidity that was determined by pyridine and FTIR, the crystal structure observed by XRD, the surface area and pore volume analyzed by BET/BJH, the surface morphology observed by TEM, the metal on the surface of catalyst observed by XPS and the product of the hydrocracking analyzed by GC-MS. Hexagonal structure of the MCM-41(100) was shown in the 2θ = 3o-5o of the diffractogram. The presence of impregnated Al and Pd observed at the 2θ = 20o and 34o, respectively. The Pd/Al-MCM-41 catalyst was more acidic than Al-MCM-41 catalyst. The surface area and pore volume of the catalyst decreased after the impregnation process. The tendency of catalytic hydrocracking of hydrocarbon produced was indicated that more amount of Palladium have more hydrocarbons aliphatic than alcohol.